Assessment of impact of regulatory guidelines on procurement lead times in world bank-funded projects in Nigeria - Effiong, Etim Augustine; Nwoke, Prof. Herbert; Ugwu, Associate Prof. Kelechi Enyinna (YAYASAN MITRA PERSADA NUSANTARA, 2025)
The purpose of this study is to examine the impact of regulatory guidelines on procurement lead times in World Bank-funded project South-South Nigeria. The study employed the survey method and stratified random sampling method to ensure representation across different stakeholders who constituted the population for the study. Questionnaires were given to the participants. Data collected were analysed using Pearson correlation techniques. The findings of research hypothesis showed that regulatory guidelines significantly positively impact procurement lead times in World Bank-funded Projects in South-South Nigeria. The change in regulatory framework leads to faster project start-ups, timely delivery of goods and services, improved contractor performance, and reduced project cost overruns. The Pearson correlation test result confirms a positive result with the value of (p= .000, r = .997, N = 229). Therefore, values ​​close to r = +1 indicate a strong (positive) linear correlation between x (regulatory guidelines, RG) and Y (procurement lead time, PL). The study recommends that regular training programs for employees and local stakeholders are necessary to improve understanding of World Bank regulations and procurement standards.